Short Communication: Molecular study on mt-DNA COX2 gene of Sumatran elephant (Elephas maximus sumatranus) - Deny Setyo Wibowo; Rini Widiyanti; Machmud Asvan; Prista Dwi Restanti; Hery Wijayanto (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Wibowo DS, Widiyanti R, Asvan M, Restanti PD, Wijayanto H. 2021. Short Communication: Molecular study on mt-DNA COX2 gene of Sumatran elephant (Elephas maximus sumatranus). Biodiversitas 22: 1063-1068. Sumatran elephant is the only subspecies of Asian elephants that receives a critically endangered status from the International Union for Conservation and Nature Resources (IUCN). Identifying the genetic marker of Sumatran elephants is, therefore, important for their conservation. This study aimed to identify the Sumatran elephant based on specific mitochondrial DNA markers of the Cytochrome c oxidase subunit II (COX2) gene. It is an exploratory research considering the limited data and research about the genetic, especially the COX2 of Sumatran elephant (Elephas maximus sumatranus). Forward and reverse sequencing of PCR products was conducted using the primary COX2 from Sumatran elephant samples. The results of the subsequent gene sequencing were aligned with the sequences of other Asian elephants from Genbank using Clustal W software and analyzed using the MEGA program version 6.06. The analysis of genetic distance based on COX2 constituent nucleotides calculated with Kimura’s two-parameter method showed that the genetic distance between Elephas maximus sumatranus and Elephas maximus outside of Sumatra was 0.25%. The phylogenetic trees analyzed using the maximum-likelihood based on nucleotide sequences showed a high homogeneity. The ratio of Elephas maximus sumatranus with Elephas maximus shows levels of nucleotide mutations which are nine nucleotides and four nucleotides. These results indicated that the COX2 gene could not identify the individual species of Sumatran elephant because of the high intraspecies homogeneity, but it detected the interspecies divergence clustered in Asian elephant clade.